Prophylactic vaccination against human papillomaviruses to prevent cervical cancer and its precursors - Arbyn, Marc; Xu, Lan; Simoens, Cindy; Martin-Hirsch, Pierre Pl (Cochrane database of systematic reviews, 2018)
Persistent infection with high-risk human papillomaviruses (hrHPV) types is causally linked with the development of cervical precancer and cancer. HPV types 16 and 18 cause approximately 70% of cervical cancers worldwide. To evaluate the harms and protection of prophylactic human papillomaviruses (HPV) vaccines against cervical precancer and HPV16/18 infection in adolescent girls and women. We searched MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL) and Embase (June 2017) for reports on effects from trials. We searched trial registries and company results' registers to identify unpublished data for mortality and serious adverse events. Randomised controlled trials comparing efficacy and safety in females offered HPV vaccines with placebo (vaccine adjuvants or another control vaccine). We used Cochrane methodology and GRADE to rate the certainty of evidence for protection against cervical precancer (cervical intraepithelial neoplasia grade 2 and above [CIN2+], CIN grade 3 and above [CIN3+], and adenocarcinoma-in-situ [AIS]), and for harms. We distinguished between the effects of vaccines by participants' baseline HPV DNA status. The outcomes were precancer associated with vaccine HPV types and precancer irrespective of HPV type. Results are presented as risks in control and vaccination groups and risk ratios (RR) with 95% confidence intervals in brackets. We included 26 trials (73,428 participants). Ten trials, with follow-up of 1.3 to 8 years, addressed protection against CIN/AIS. Vaccine safety was evaluated over a period of 6 months to 7 years in 23 studies. Studies were not large enough or of sufficient duration to evaluate cervical cancer outcomes. All but one of the trials was funded by the vaccine manufacturers. We judged most included trials to be at low risk of bias. Studies involved monovalent (N = 1), bivalent (N = 18), and quadrivalent vaccines (N = 7). Most women were under 26 years of age. Three trials recruited women aged 25 and over. We summarize the effects of vaccines in participants who had at least one immunisation.Efficacy endpoints by initial HPV DNA statushrHPV negativeHPV vaccines reduce CIN2+, CIN3+, AIS associated with HPV16/18 compared with placebo in adolescent girls and women aged 15 to 26. There is high-certainty evidence that vaccines lower CIN2+ from 164 to 2/10,000 (RR 0.01 (0 to 0.05)) and CIN3+ from 70 to 0/10,000 (RR 0.01 (0.00 to 0.10). There is moderate-certainty evidence that vaccines reduce the risk of AIS from 9 to 0/10,000 (RR 0.10 (0.01 to 0.82).HPV vaccines reduce the risk of any CIN2+ from 287 to 106/10,000 (RR 0.37 (0.25 to 0.55), high certainty) and probably reduce any AIS lesions from 10 to 0/10,000 (RR 0.1 (0.01 to 0.76), moderate certainty). The size of reduction in CIN3+ with vaccines differed between bivalent and quadrivalent vaccines (bivalent: RR 0.08 (0.03 to 0.23), high certainty; quadrivalent: RR 0.54 (0.36 to 0.82), moderate certainty). Data in older women were not available for this comparison.HPV16/18 negativeIn those aged 15 to 26 years, vaccines reduce CIN2+ associated with HPV16/18 from 113 to 6 /10,000 (RR 0.05 (0.03 to 0.10). In women 24 years or older the absolute and relative reduction in the risk of these lesions is smaller (from 45 to 14/10,000, (RR 0.30 (0.11 to 0.81), moderate certainty). HPV vaccines reduce the risk of CIN3+ and AIS associated with HPV16/18 in younger women (RR 0.05 (0.02 to 0.14), high certainty and RR 0.09 (0.01 to 0.72), moderate certainty, respectively). No trials in older women have measured these outcomes.Vaccines reduce any CIN2+ from 231 to 95/10,000, (RR 0.41 (0.32 to 0.52)) in younger women. No data are reported for more severe lesions.Regardless of HPV DNA statusIn younger women HPV vaccines reduce the risk of CIN2+ associated with HPV16/18 from 341 to 157/10,000 (RR 0.46 (0.37 to 0.57), high certainty). Similar reductions in risk were observed for CIN3+ associated with HPV16/18 (high certainty). The number of women with AIS associated with HPV16/18 is reduced from 14 to 5/10,000 with HPV vaccines (high certainty).HPV vaccines reduce any CIN2+ from 559 to 391/10,000 (RR 0.70 (0.58 to 0.85, high certainty) and any AIS from 17 to 5/10,000 (RR 0.32 (0.15 to 0.67), high certainty). The reduction in any CIN3+ differed by vaccine type (bivalent vaccine: RR 0.55 (0.43 to 0.71) and quadrivalent vaccine: RR 0.81 (0.69 to 0.96)).In women vaccinated at 24 to 45 years of age, there is moderate-certainty evidence that the risks of CIN2+ associated with HPV16/18 and any CIN2+ are similar between vaccinated and unvaccinated women (RR 0.74 (0.52 to 1.05) and RR 1.04 (0.83 to 1.30) respectively). No data are reported in this age group for CIN3+ or AIS.Adverse effectsThe risk of serious adverse events is similar between control and HPV vaccines in women of all ages (669 versus 656/10,000, RR 0.98 (0.92 to 1.05), high certainty). Mortality was 11/10,000 in control groups compared with 14/10,000 (9 to 22) with HPV vaccine (RR 1.29 [0.85 to 1.98]; low certainty). The number of deaths was low overall but there is a higher number of deaths in older women. No pattern in the cause or timing of death has been established.Pregnancy outcomesAmong those who became pregnant during the studies, we did not find an increased risk of miscarriage (1618 versus 1424/10,000, RR 0.88 (0.68 to 1.14), high certainty) or termination (931 versus 838/10,000 RR 0.90 (0.80 to 1.02), high certainty). The effects on congenital abnormalities and stillbirths are uncertain (RR 1.22 (0.88 to 1.69), moderate certainty and (RR 1.12 (0.68 to 1.83), moderate certainty, respectively). There is high-certainty evidence that HPV vaccines protect against cervical precancer in adolescent girls and young women aged 15 to 26. The effect is higher for lesions associated with HPV16/18 than for lesions irrespective of HPV type. The effect is greater in those who are negative for hrHPV or HPV16/18 DNA at enrolment than those unselected for HPV DNA status. There is moderate-certainty evidence that HPV vaccines reduce CIN2+ in older women who are HPV16/18 negative, but not when they are unselected by HPV DNA status.We did not find an increased risk of serious adverse effects. Although the number of deaths is low overall, there were more deaths among women older than 25 years who received the vaccine. The deaths reported in the studies have been judged not to be related to the vaccine. Increased risk of adverse pregnancy outcomes after HPV vaccination cannot be excluded, although the risk of miscarriage and termination are similar between trial arms. Long-term of follow-up is needed to monitor the impact on cervical cancer, occurrence of rare harms and pregnancy outcomes.